Metformin and l-glutamine ameliorate pancreatic damage induced by chronic nicotine exposure in adult male albino rats - Abdel-Mohsen Abdel-Aziz, Eman; Y. A. Hussein, Asmaa; A Elnoury, Heba (International Journal of Pharmacology and Toxicology, 2019)
Nicotine is a major addictive component of tobacco and cigarettes. It is believed to play a major role in the development of many diseases of pancreas including induction of pancreatitis and pancreatic cancer. This study was designed to assess the ameliorative effect of metformin & L-glutamine administered either individually or in combination on pancreatic damage induced by chronic exposure to nicotine. Fifty-six adult male albino rats were divided into 7 weight matched groups of 8 animals per each group and treated once daily for a period of 10 weeks according to the following protocol; group I (normal control): left without intervention ; they were allowed to free access to balanced diet & distilled water for the end of the experiment, group II (metformin treated group; Met): metformin was administrated to normal rats at a dose of (150 mg/kg /day /orally); group III (glutamine group ; LG): in which L-glutamine was given to normal rats at a dose of 500 mg/kg by oral gavage); group IV (diseased non-treated group ;Nicotine) were injected subcutaneously with nicotine (1.5 mg/kg/day after day) to induce pancreatitis; group V (Nicotine +Met), VI (Nicotine +LG) &VII (Nicotine +Met + LG) were treated by (Nicotine +Met, Nicotine +LG & Nicotine +Met + LG respectively) by the same doses and routs described above. At the end of the experiment the following biochemical parameters were measured (fasting blood glucose, plasma insulin level, serum amylase and lipase level, tumor necrosis factor alpha (TNF-α), heat shock protein 70 (HSP70) & reduced glutathione; GSH) to investigate the protective effect of either or both drugs on pancreas. Additionally, histopathological evaluations of pancreatic tissues were assessed. The current study documented the damaging effect of nicotine on pancreas evidenced by significant increase of (blood glucose level due to decrease in plasma insulin level, serum lipase and amylase & TNF-α levels along with significant reduction of GSH in pancreatic tissue & heat shock protein -70. This was accompanied by histopathological alteration in pancreatic tissue. The previously mentioned parameters illustrate partial significant improvement in concomitant administration of individual or both metformin & L glutamine along with nicotine. In conclusion, co- supplementation of metformin and L glutamine documented to be anti-hyperglycemic, antioxidant and anti-inflammatory which can ameliorate the damaging effect of nicotine on pancreas. The combination use of both drugs produces more protective effect than each other alone.